RELEVANCE OF STUDYING THE CAUSES OF PRIMARY DISABILITY OF THE POPULATION OF THE RUSSIAN FEDERATION AND KUZBASS - Абрамов, Николай Владимирович; Петров, Андрей Георгиевич; Филимонов, Сергей Николаевич; Семенихин, Виктор Андреевич; Хорошилова, Ольга Владимировна; Денисова, Светлана Викторовна (Medicine in Kuzbass, 2025)
Primary disability is one of the main indicators of health. The level of primary disability of the population is directly dependent on the level of socio-economic development of society, the environmental well-being of each individual region and the country as a whole, the quality and availability of medical and pharmaceutical care, including high-tech, preventive measures.
Keywords: primary disability; causes of disability; population of the Russian Federation and Kuzbass